Pluralism and the idea of balance in Eastern and Western philosophies - Darwish, Hasan (My University, 2016)
Balance, in the broadest sense, can be taken to be a desirable intermediary point or state between two or more opposing points or states. This thesis demonstrates and argues that the idea of balance is ubiquitous — it appears in nature, the sciences, religions and common sense beliefs. Furthermore, it goes beyond this by attempting to extract this idea from prominent ethical theories — both those in the West and East, namely, Kantian Ethics, Aristotelian Virtue Ethics, Utilitarianism, Islam, Taoism, Hinduism, Confucianism and Buddhism. In the sciences and natural world, molecules, objects or plants are simply forced towards the trajectory of balance. This descriptively gives us some forms of balance. Ethically, many theories, as I show in the essay, strive towards balance and thus normatively prescribe balance as the index of choice, conduct and action. I draw some conclusion from this, which is that a balanced conduct and action lead to ethical action, whilst an imbalanced conduct and action result in an unethical action. Objections to this notion are discussed and addressed in various stages of the essay. At the end of the essay, I apply this reasoning to issues in applied ethics, namely, terrorism, wealth inequality and the environment
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the degree of Master of Arts, Applied Ethics for Professionals Johannesburg, 2016
Keywords: Applied ethics.